Pengaruh Multiple Intelligences dan Karakter Terhadap Pecapaian Mahasiswa FIP Universitas Negeri Medan - Lumbanraja, Sri Rezeki; Dharma, Irtiyah Nazwa; Sigalingging, Jelita R; Muslihani, Khaira; Salsabil, Nazwaa; Manalu, Yolanda Br; Lumbanraja , Sri Rezeki (CV. Eracita Grup, 2025)
This study aims to analyze the influence of multiple intelligences and character on the achievement of students at the Faculty of Education, State University of Medan. The study employed a quantitative approach with an explanatory research design. The population comprised all students of the Faculty of Education at the State University of Medan, with samples selected using proportional random sampling. Data were collected through questionnaires to measure multiple intelligences and character, as well as academic documentation to measure student achievement. Data analysis was conducted using multiple linear regression after fulfilling the prerequisite assumption tests. The results indicate that, partially, multiple intelligences do not have a significant effect on student achievement, whereas character has a positive and significant effect on student achievement. However, the simultaneous test results show that multiple intelligences and character together have a significant effect on student achievement. These findings suggest that student achievement is the result of an interaction between the potential of multiple intelligences and character, with character acting as the dominant factor that drives the optimization of such potential. The study concludes that improving student achievement should not be carried out partially, but requires a holistic approach through continuous character development and more optimal management of multiple intelligences in the higher education learning process.